Assessment of Immunization of Under Five Children of Tribal and Non-Tribal Rural Communities in Southern Rajasthan - Dilip Kumar L; Krishan Kumar Sharma; K A Varghese (Medsci Publications, 2018)
Background: The impact of immunization has not been uniform across different sections of the society, despite thrust on Expanded Programme of Immunization (EPI) since long back. This study was held to assess the level of knowledge and actual practice of immu- nization by tribal and non-tribal mothers of under five children in a rural belt of southern Rajasthan. Methods: The study is based on a cross section of sample house- holds representing the two social groups, viz tribal and non-tribal households with atleast one under five children in a rural belt of southern Rajasthan. In all 200 families, 100 tribal and 100 non- tribal families were selected randomly for the study. The required information was collected on a well structured questionnaire. Results: While 100 percent non-tribal mothers have knowledge about immunization of children, about 50 percent tribal mothers knew something about mode of giving vaccination doses, place of its availability and likely post immunization problems for chil- dren. In non-tribal area 86.4 percent under five children were fully immunized, against 28.2 percent in tribal families. Conclusions: For programmes like immunization of children, the group based approach would be more rewarding compared to area approach due to poor socio-economic development of mar- ginalized group like tribals.